Facial skin condition, health and perception in Malaysian Chinese - Tan, Kok Wei (2016)
Skin texture and colour play an important role in the judgment of apparent health (Fink, Grammer, & Thornhill, 2001; Jones, Little, Burt, & Perrett, 2004; Matts, Fink, Grammer, & Burquest, 2007; Samson, Fink, & Matts, 2010; Stephen, Coetzee, Law Smith, & Perrett, 2009a; Stephen, Coetzee, & Perrett, 2011), and have been linked to aspects of physiological health, including fitness, immunity and fertility (Armstrong & Welsman, 2001; Jones et al., 2015; Stephen et al., 2011).